Enhancing Vocational Teachers' Competence: A Cisco Packet Tracer-Based Simulation Model for Network Administration - Heriyanto, Heriyanto; Wulandari, Dian; Desianti, Lisa Chandrasari (JURNAL AL-TANZIM, 2025)
This study aims to improve teacher competence in network system administration subjects at vocational high schools by developing a Cisco Project Tracer-based simulation learning media and testing its feasibility, practicality, and effectiveness.  This research employs the Research and Development method, adopting the ADDIE model. Quantitative data were analysed using a paired sample t-test and the N-Gain Score calculation. The expert validation results showed that the developed media achieved an average score of 89%, indicating "highly feasible".  The effectiveness test indicated a significant increase in teacher competence, with an N-Gain Score of 0,61 (medium category). Teacher responses regarding the practicality of the media were also highly positive, with 90% agreeing that the media was easy to use and relevant to learning needs. These findings show that the developed simulation media are not only feasible but also effective and practical in enhancing teachers' pedagogical and professional competence.  The study concludes that the Cisco Packet Tracer-based simulation media developed is valid, practical, and effective for improving the competence of Network System Administration teachers.